Patrones lingüísticos y elementos básicos de lenguaje durante el proceso de enseñanza aprendizaje, en los estudiantes de octavo año de la Unidad Educativa Guaranda, del cantón Guaranda, provincia Bolívar, en el periodo lectivo 2024-2025. - Aimacaña Tello, Maria Fernanda (2025)
This research focuses on examining the linguistic patterns and key language elements in the teaching-learning process of eighth-grade students at Unidad Educativa Guaranda, located in the province of Bolívar, Ecuador, during the 2024– 2025 academic year. This study adopted a mixed-methods approach, combining qualitative and quantitative methods through surveys administered to a sample of 150 students from classrooms "A, B, C, D, E, F" and semi- structured interviews with five Language and Literature teachers. The findings revealed that while more than half of the students understand grammatical rules, they face significant challenges in their practical application. Additionally, fewer than half of the students struggle to form coherent sentences, and 36% do not review their written work before submission. It was also observed that only 40% of students spend time reading outside the classroom, limiting their exposure to diverse linguistic models. On the other hand, teachers pointed out that the main learning difficulties include a lack of habits for independently revising work, limited vocabulary, and minimal participation in oral activities. Finally, a guide featuring innovative pedagogical strategies was developed to dynamically strengthen communicative competencies, aiming to bridge the gap between theoretical knowledge and practical application, thereby improving students’ academic performance and skills.